Assesment of self medication in Academics from Medical School (Research, Society and Development, 2020)
Evaluate the practices of self-medication in medical students, as well as factors, frequency and which are the most frequent medications. A quali-quantitative cross-sectional study in which about 200 students answered a questionnaire containing multiple choice questions about the practice of self-medication. For the statistical analysis of the data, the chi-square test was used and the 95% confidence index was used. The 146 students who administered a medication in this period, 61 (41.7%) reported that the medication was not prescribed by a physician / dentist. The prevalence of self-medication among students who administered medication in the last 6 months was 88%. The most commonly used drugs were analgesics and muscle relaxants. It is worth emphasizing the indiscriminate use of antibiotics, one of the biggest and dangerous consequences is bacterial resistance, which impedes the effectiveness of the treatment and the delay in curing the patient. Self-medication rate among students was high, similar to other studies observed. This theme requires intervention practices of academic educational structures, which need to be based on effective methods and protocols that focus on favoring medical students, alerting them on the risk of self-medication.